Transformational Leadership: The Practice of Principals in Islamic Schools - Mu'alimin Mu'alimin; Moh Anwar (Ta'dib: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to analyze and find formulations of change leadership practices in Islamic schools at SD Khadijah Surabaya and SD Muhammadiyah 1 Sidoarjo in responding to educational demands and changes. Using a qualitative approach to the type of multi-case study, data were collected through observation, interviews and documentation. Data analysis through a single case to multi-case findings with an interactive model through data reduction, presentation and conclusion. Data validations used member check, source and method triangulation. The research findings showed that the practice of Islamic school principal leadership was carried out through strengthening the school's vision and mission by making organizational values the school's goals, seeing change as a challenge by making changes to aspects of the curriculum, and collaborating with educational institutions at the national, regional and international levels